Design and Implementation of a Multi Sensor Based Vehicle Safety System Using RFID and Microcontroller for Accident Prevention - Ledyana Fitriani; Athirah Rusadi; Rizki Maulana Martin (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Vehicle safety is a crucial aspect of driving safety, especially given the growing number of drivers whose abilities may increase the risk of traffic accidents. This study aims to design and build a microcontroller-based safety system capable of providing early warnings and taking automatic actions to prevent accidents. The developed system utilizes an ATMega8535 microcontroller integrated with several types of sensors, including an SRF04 ultrasonic sensor for distance detection, a phototransistor for speed measurement, and an LM35 sensor for monitoring engine temperature, and is equipped with a security system using RFID. The research method employed involves the design and implementation of an embedded system using a prototype approach. Data from the sensors is processed by the microcontroller to determine whether conditions are safe or hazardous based on specific threshold values. If the distance to an object is less than 11 cm, the engine temperature exceeds 80°C, or the vehicle speed exceeds the specified limit, the system will issue a warning via a buzzer and automatically activate the braking system. Vehicle status information is displayed in real-time on an LCD. Test results show that the system performs very well in terms of detecting conditions and responding quickly, with an average response time of approximately 1–1.4 seconds under various sensor test conditions. The system is also capable of efficiently integrating security (RFID) and safety (multi-sensor) functions into a single device. The conclusion of this study is that the designed system can improve driving safety by providing early warnings and taking actions to minimize the occurrence of accidents.